Introduction of dual elements in vocational educationand training in Paraguay - Correa Sarmiento, Constanza [Verfasser]; Klede, Martin [Verfasser]; Schwarz, Henrik [Verfasser] (My University, 2019)
"The objective of the project 'MoPaDual - Modelo paraguayo de Formación Dual' is to establish dual vocational education and training in Paraguay. At the request of the country’s government, BIBB is advising the Paraguayan Ministry of Labour on the establishment of institutional foundations and on the development of VET standards. This article describes the initial results to emerge from the cooperation, taking the development of occupational profiles and curricula as an example." (Author's abstract ; BIBB-Doku)
Einführung dualer Elemente in die Berufsausbildung Paraguays
Keywords: S System beruflicher Bildung; I 1.1 Systemberatung; I 2.3.3 Lateinamerika; Berufsbildungssystem; Betriebliche Berufsausbildung; Internationale Zusammenarbeit; Bundesinstitut für Berufsbildung; Systemberatung [Berufsbildung]; Paraguay